Crime against women: a search for peaceful solution - Chattoraj, B. N. (Lok Nayak Jayaprakash Narayan National Institute of Criminology and Forensic Science, Ministry of Home Affairs, 2007)
Contributed papers presented at the National Seminar on "Crime Against Women: a Search for Peaceful Solution" held from December 6-8, 2005, New Delhi